The Prevalence of Interpersonal Violence (IPV) Against Women and its Associated Variables: An Exploratory Study in the Rongo Sub-County of Migori County, Kenya - Morris, Miller (Journal of interpersonal violence, 2022)
Interpersonal violence (IPV) within intimate partner relationships and gender-based violence remain major public health problems worldwide; 44.8% of Kenyan women have reported experiencing IPV beginning after the age of 15 years (National Bureau of Statistics Nairobi, Kenya, 2015). Combatting IPV and its sequelae is integral to promoting gender equality, a key target of the Sustainable Development Goals. We quantify the lifetime prevalence of IPV among women in two rural Kenyan communities, as well as factors associated with IPV in this area, such as educational attainment and severe depression. We conducted a cross-sectional population-based survey of households in the North and East Kamagambo wards of Migori County, Kenya in May 2018. A questionnaire regarding IPV was given to female respondents. Group-wise comparisons and multiple logistic regression analyses were performed to describe community prevalence and factors associated with IPV against women. A total of 873 women completed questions about IPV, representing a population estimate of 11,252 women in the study area. Lifetime IPV prevalence in the study area was 60.3%. Variables associated with IPV included involvement in a polygamous marriage (adjusted odds ratio [aOR]: 1.81; 95% confidence interval [CI]: [1.13, 2.88]; p = .013), attaining six or fewer years of education (aOR: 1.84; 95% CI: [1.27, 2.66]; p = .001), and IPV exposure in girlhood (aOR: 1.59; 95% CI: [1.12, 2.28]; p = .011). IPV was independently associated with experience of emotional abuse (OR: 11.22; 95% CI: [7.02, 17.95]; p < .001) and severe depression (OR: 3.51; 95% CI: [1.03, 11.97]; p = .045). Violence against women is a public health emergency in Migori County, Kenya. Low educational attainment, IPV exposure in girlhood, and polygamy were significantly associated with experience of IPV. Our results provide hyper-local data necessary for targeted interventions and generalizable data with sampling methods for use by other implementing organizations in sub-Saharan Africa.